Peningkatan Kompetensi Pegawai Melalui Pengembangan Sumber Daya Manusia dan Kepuasan Kerja - Deby Rahma Aulya; Muhamad Azis Firdaus; Hendri Maulana (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the effect of Human Resource Development (HRD) and job satisfaction on employee competence at the Nutrition Fulfillment Service Unit (SPPG) in the Ciasmara Region. The study employed a quantitative method with an associative approach. The research population consisted of 55 active employees, all of whom were included as the sample using a saturated sampling technique. Data were collected through questionnaires and analyzed using validity, reliability, classical assumption, multiple linear regression, correlation coefficient, coefficient of determination, and hypothesis tests. The findings indicate that HRD has a positive and significant effect on employee competencen. In addition, job satisfaction also has a positive and significant effect on employee competence. Simultaneously, both variables exert a positive and significant influence on employee competence. The findings imply that the institution should implement systematic HRD programs and foster a condusive woek environment to enhance job satisfaction, thereby enabling employee competence to develop optimally.